Pengaruh Dongeng Terhadap Regulasi Emosi Pada Anak Usia Dini - Delzi Nurhafifah; Saffany Puteri Haniyashfira; Salma Novianti; Tysem Wani Calara Nainggolan; Prima Aulia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to examine the effect of giving fairy tales on the emotional regulation of kindergarten-aged children. The research method used was pre-experimental with a quantitative approach. The research subjects were children aged 4-6 years at the UNP Padang Laboratory Development Kindergarten. The treatment in the form of giving fairy tales was carried out for 4 consecutive days, with pre-test measurements before treatment and post-test after treatment. The data collection instrument uses a Likert scale formulated positively and negatively to measure children's emotional regulation. The results of the study showed that there was significant development in children's emotional regulation after receiving treatment in the form of giving fairy tales. This can be seen from the difference in pre-test and post-test results which show an increase in scores on the Likert scale. Evaluation of children's emotions is carried out after each storytelling session to monitor the development of their emotional regulation. Researchers also gave rewards to children as a form of appreciation for their participation in the research. This research contributes to the understanding of the influence of fairy tales on the emotional regulation of kindergarten-aged children. The implication of this research is the importance of paying attention to environmental factors and learning methods that can influence children's emotional development. It is hoped that the results of this research can become a basis for developing better educational programs to improve emotional regulation in early childhood.